Assessment of human exposure to benzophenone-type UV filters: A review. (September 2022) - Mao, Jason Feijian; Li, Wenxuan; Ong, Choon Nam; He, Yiliang; Jong, Mui-Choo; Gin, Karina Yew-Hoong
Graphical abstract: Highlights: Most of the human exposure studies are related to urine. Human burden, possible exposure and biotransformation pathways were discussed. BP-3 is the most popular species. Prenatal exposure and transplacental transfer of BPs are possible. Various factors can affect body burdens of BPs. Abstract: To avoid the harmful effects of UV radiation, benzophenone-type UV filters (BPs) are widely used in personal care products and other synthetic products. Biomonitoring studies have shown the presence of BPs in various human biological samples, raising health concerns. However, there is a paucity of data on the global human exposure to this group of contaminants. In this study, we compiled data on the body burden of BPs along with the possible exposure routes and biotransformation pathways. BPs can easily penetrate the skin barrier and thus, they can be absorbed through the skin. In the human body, BPs can undergo Phase I (mainly demethylation and hydroxylation) and Phase II (mainly glucuronidation and sulfation) biotransformations. From a total of 158 studies, most of the studies are related to urine (concentration up to 92.7 mg L –1 ), followed by those reported in blood (up to 0.9 mg L –1 ) and milk (up to 0.8 mg L –1 ). Among BPs, benzophenone-1 and benzophenone-3 are the most commonly detected congeners. The body burden of BPs is associated with various factors, including the country of residence, lifestyle, income, education level, and ethnicity. The presence of BPs in maternal urine (up to 1.1 mg L –1 ), placenta (up to 9.8 ng g −1 ), and amniotic fluid (up to 15.7 μg L –1 ) suggests potential risks of prenatal exposure. In addition, transplacental transfer of BPs is possible, as demonstrated by their presence in maternal serum and cord serum. The possible association of BPs exposure and health effects was discussed. Future human biomonitoring studies and studies on the potential health effects are warranted. Overall, this review provides a summary of the global human exposure to BPs and can serve as supporting evidence to guide usage in order to protect humans from being exposed to BPs.